EFEKTIFITAS KEDALAMAN TERHADAP NILAI LUGEUN PILOT HOLE (PH8) PADA PEKERJAAN GROUTING PROYEK BENDUNGAN CIPANAS PAKET 1 - Wulandari, Wulandari; Nofrizal, Nofrizal; Arman. A, Arman. A (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Grouting is a ground improvement method used to increase the bearing capacity and reduce the permeability of dam foundations. This study aims to analyze the effect of depth on the Lugeon value in Pilot Hole 8 (PH8) during the grouting work at the Cipanas Dam Project Package 1. The method involves conducting Water Pressure Tests (WPT) to measure Lugeon values at various grouting depths, ranging from 5 to 50 meters with 5-meter intervals. The results showed that pre-grouting Lugeon values ranged from 2.60 to 35.52 Lu, while post-grouting values significantly decreased to below 3 Lu. The grouting effectiveness, based on the reduction of permeability coefficients, showed dominantly >80%, with the highest effectiveness reaching 92.10% at a depth of 30 meters. These findings indicate that a depth of 30 meters with a 3-meter interval is the most effective in reducing water seepage according to the design standards. This research provides practical insights for determining the optimal depth and efficiency of grouting works in dam construction projects across Indonesia.Keywords: Grouting, Lugeon, Permeability, Depth, Effectiveness, Cipanas Dam